Refractory diffuse large B‐cell lymphoma after first‐line immuno‐CT: Treatment options and outcomes. Issue 3 (2nd May 2018) - Filliatre‐clement, Lauriane; Maucort‐Boulch, Delphine; Bourbon, Estelle; Karlin, Lionel; Safar, Violaine; Bachy, Emmanuel; Sesques, Pierre; Ferrant, Emmanuelle; Bouafia, Fadela; Lazareth, Anne; Ghergus, Dana; Coiffier, Bertrand; et al.
Abstract: In the rituximab era, one‐third of diffuse large B‐cell lymphoma patients experience relapse/refractory disease after first‐line anthracycline‐based immunochemotherapy. Optimal management remains an unmet medical need. The aim of this study was to report the outcomes of a cohort of refractory patients according to their patterns of refractoriness and the type of salvage option. We performed a retrospective analysis, which included 104 diffuse large B‐cell lymphoma patients treated at Lyon Sud University Hospital (2002‐2017) who presented with refractory disease. Refractoriness was defined as progressive/stable disease during first‐line treatment (primary refractory, N = 47), a partial response after the end of first‐line treatment that required subsequent treatment (residual disease, N = 19), or relapse within 1 year of diagnosis after an initial complete response (CR) (early relapse, N = 38). The 2‐year overall survival (OS) rates for primary refractory, early relapse, and residual disease patients were 27%, 25%, and 52%, respectively, while the event‐free survival rates for those groups were 13%, 13%, and 42%, respectively. In a univariate analysis, lactate dehydrogenase level, Ann Arbor stage, poor performance status, high age‐adjusted International Prognostic Index score, and age > 65 years were associated with shorter OS. The use of rituximab and platinum‐based chemo during the first salvage treatment was associated with prolonged OS. In a multivariate analysis, age (HR:2.06) and rituximab use (HR:0.54) were associated with OS. Among patients <65 years who achieved a CR, autologous stem‐cell transplant was associated with higher 2‐year OS (90% vs 74%, P = 0.10). Patients who were treated with a targeted therapy in the context of a clinical trial after second‐line treatment had a higher 2‐year OS (34% vs 19%, P = 0.06). In conclusion, patients with primary refractory disease or early relapse have very poor outcomes but may benefit from rituximab retreatment during the first salvage treatment.